OPTIMAL PALETTE CREATE WITH THE SPECIFIED NUMBER OF COLORS USING OCTREE QUANTIZATION - Mohammed, Faisel (Iraqi Journal of Science, 2024)
In the current research work, improved and fast method to get a good approximation of the most important 256 colors of a RGB-Picture was introduced. In this paper, we propose a spatially-adaptive optimum octree quantization method for robust color printing. The goal of spatially-adaptive octree quantization is to use quantization well-suited for smooth areas, and to use octree quantization method better suited for edges. It may be useful for digital image compression, graphics- and game programmers. Also, this includes reduction of the overall number of colors, quantization or patterning the reduced number of colors, generating bitmap images, and even handling Boolean (on/off) transparency. The results show the suggested adaptive octree data-structure is useful for color-quantization.